Production methods of Van der Waals heterostructures based on transition metal dichalcogenides - Qi, Haimei (2018)
Two dimensional (2D) materials have gained significant attention since the discovery of graphene in 2004. Layered transition metal dichalcogenides (TMDs) have become the focus of 2D materials in recent years due to their wide range of chemical compositions and a variety of properties. These TMDs layers can be artificially integrated with other layered materials into a monolayer (lateral) or a multilayer stack (vertical) heterostructures. The resulting heterostructures provide new properties and applications beyond their component 2D atomic crystals and many exciting experimental results have been reported during the past few years. In this review, we present the various synthesis methods (mechanical exfoliation, physical vapor transport, chemical vapor deposition, and molecular beam epitaxy method) on van der Waals heterostructures based on different TMDs as well as an outlook for future research.